Proceedings of the 9th Annual Cyber and Information Security Research Conference on - CISR '14 2014
DOI: 10.1145/2602087.2602107
|View full text |Cite
|
Sign up to set email alerts
|

Implementing moving target IPv6 defense to secure 6LoWPAN in the internet of things and smart grid

Abstract: The growing momentum of the Internet of Things (IoT) has shown an increase in attack vectors within the security research community. We propose adapting a recent new approach of frequently changing IPv6 address assignment to add an additional layer of security to the Internet of Things. We examine implementing Moving Target IPv6 Defense (MT6D) in IPv6 over Low-Powered Wireless Personal Area Networks (6LoWPAN); a protocol that is being used in wireless sensors found in home automation systems and smart meters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Since IoT concerns severe resource constraints because most of them are mobile devices, developing lightweight shufflingbased MTD is a key concern in IoT-based MTD. Main Attacks: The most common attack behaviors considered in IoT-based MTD approaches are reconnaissance (scanning) attacks [101,140,162,163] although some conventional attacks, such as cryptographic attacks [26], are also considered. Although more intelligent, smarter attack behaviors have been extensively studied in IoT environments, IoT-based MTD techniques dealing with APT attacks have been rarely studied [107].…”
Section: B Internet-of-things (Iot)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since IoT concerns severe resource constraints because most of them are mobile devices, developing lightweight shufflingbased MTD is a key concern in IoT-based MTD. Main Attacks: The most common attack behaviors considered in IoT-based MTD approaches are reconnaissance (scanning) attacks [101,140,162,163] although some conventional attacks, such as cryptographic attacks [26], are also considered. Although more intelligent, smarter attack behaviors have been extensively studied in IoT environments, IoT-based MTD techniques dealing with APT attacks have been rarely studied [107].…”
Section: B Internet-of-things (Iot)mentioning
confidence: 99%
“…Key Methodologies: Casola et al [26] identified reconfigurable architectural layers to develop shuffling-based or diversity-based MTD in terms of security and physical layers. IP shuffling-based MTD has been developed based on IPv6 for IoT devices [140,162,163]. Mahmood and Shila [101] used minimal trusted code in an IoT device, which can be erased after it was used in order to ensure security in a resourceconstrained IoT environment.…”
Section: B Internet-of-things (Iot)mentioning
confidence: 99%
See 1 more Smart Citation
“…Casola et al [10] proposes diversification of the network security protocols (Network) and firmware (Platform). The most explored strategy has been IPv6 address randomization [11]- [13] (Network). Mahmood et al [14] proposed code execution partitioning and diversification (Software).…”
Section: A Background: Mtd Fundamentalsmentioning
confidence: 99%
“…Therefore, the objective function cannot provide the optimal route with a single routing metric. The aim of this study is to introduce multiple routing metrics in routing decision-making by fuzzy logic theory to design and implement the objective function, and use Cooja simulation software to simulate and analyze the fuzzy optimization routing performance [2][3] .…”
Section: Introductionmentioning
confidence: 99%